The passion of Darkly Noon - Bicat, Nick 1949- (Lionsgate, 2011)
A young man, Darkly Noon, survives a brutal attack on his religious group, but is found by a young truck driver, Jude, roaming the forest. Jude brings him to the home of Callie and her lover Clay, to whom he delivers supplies. Callie decides to nurse Darkly, but he develops a strange obsession with her as he recovers. When Callie wants to protect her relationship with Clay, Darkly goes from despair to madness and finally into violence. At the end Callie is left to roam
Bildformat 1.33:1
Orig.: Großbritannien, Deutschland, Belgien
Keywords: Film